Case report: mismatch repair proficiency and microsatellite stability in gastric cancer may not predict programmed death-1 blockade resistance. Issue 1 (December 2016) - Chen, Kuo-Hsing; Yuan, Chang-Tsu; Tseng, Li-Hui; Shun, Chia-Tung; Yeh, Kun-Huei
Abstract Background Anti-programmed death-1 therapy has poor efficacy in mismatch repair-proficient (pMMR) colorectal cancers; however, its efficacy in pMMR gastric cancers remains undetermined. Here, we report the case of a patient with pMMR and microsatellite-stable gastric cancer who exhibited a partial response to salvage anti-programmed death-1 therapy with pembrolizumab. Case presentation Initially, the patient underwent subtotal gastrectomy 4 years ago for early-stage gastric cancer (pT1bN2M0, stage IIA). Immunohistochemical analysis of the tumor revealed strongly positive for HER2/neu. He had received trastuzumab plus pertuzumab, cisplatin, and capecitabine for recurrent tumors since September 2014 for 15 cycles. Disease progression of gastric cancer was found in August 2015. Since September 2015, the patient has received pembrolizumab monotherapy (200 mg as a fixed dose, every 3 weeks) for 3 months and the repeat computed tomography demonstrated a confirmed partial response. The plasma carcinoembryonic antigen also decreased dramatically. Both immunohistochemistry and a polymerase chain reaction-based method revealed that the patient had pMMR gastric cancer. Conclusions This case report provides the first report that mismatch repair-proficient and microsatellite-stable gastric cancers can respond well to anti-PD-1 monotherapy and indicates both markers may not sufficiently be predictive of anti-PD-1 therapy resistance in gastric cancer.